Easy-to-read: folk and fairy tale plays - Pugliano, Carol (JeffersonC City. MO : Scholastic Professional Books, 1997)
Build literacy with reproducible plays based on classic stories.
Includes cross-curriculum extension activities
Keywords: Plays -- Study and teaching